Solid Concentration as a Main Proxy for Basal Force Fluctuations Generated by Highly Concentrated Sediment Flows. Issue 1 (3rd January 2023) - Piantini, M.; Gimbert, F.; Korkolis, E.; Rousseau, R.; Bellot, H.; Recking, A.
Abstract: Sediment flows generate ground vibrations by exerting force fluctuations on the riverbed. Linking force fluctuations to properties of highly concentrated sediment flows, however, remains particularly challenging due to complexities arising from grain‐to‐grain interactions. Here, we conduct downscaled flume experiments in which we specifically measure force fluctuations and local seismic vibrations together with flow properties of highly concentrated sediment flows at high spatial and temporal resolution. We observe hysteresis behaviors between force fluctuations amplitude and flow surface elevation and mass that occur during complex changes in internal flow dynamics. By contrast, force fluctuations amplitude exhibits a unique negative relationship with solid concentration. We suggest this is due to the rheology of dense granular flows, where solid concentration is a proxy for particle agitation. We therefore advance that solid concentration should be incorporated in seismic models of such sediment flows as a key parameter describing inter‐particle collisions and impacts to the bed. Plain Language Summary: During their journey across the landscape, rivers convey varying amounts of sediments. As they are transported, sediments impact the riverbed and generate seismic waves through exerting force fluctuations on the ground. The amplitude of force fluctuations is thought to be linked to the characteristics of the sediment flow such as grain sizes, sediment flux, thickness and velocity. Quantifying those links, however, remains challenging, particularly for highly concentrated sediment flows in which the numerous grains being transported strongly interact with each other. Here, we conduct laboratory experiments with the aim to understand how the generation of force fluctuations by highly concentrated sediment flows is influenced by grain‐to‐grain interactions, vertical distribution of grain sizes and velocities. Despite apparent complexities in the experimentally reproduced sediment flows, we find that solid concentration is the key parameter describing the amplitude of force fluctuations. We advance that this is due to solid concentration being linked with particle agitation, which tells us about the capability of particles to collide with each other and impact the riverbed. This finding provides grounds for improving theoretical models linking the properties of highly concentrated flows with the generated seismic signal. Key Points: We investigate the force fluctuations generated by highly concentrated sediment flows exhibiting complex changes in internal dynamics We observe a unique negative relationship between the solid concentration and the amplitude of force fluctuations We suggest solid concentration should be incorporated in seismic models as a key parameter describing particle agitation